Calreticulin Is Essential for Cardiac Development - Mesaeli, Nasrin (The Rockefeller University Press, 1999)
Calreticulin is a ubiquitous Ca(2+) binding protein, located in the endoplasmic reticulum lumen, which has been implicated in many diverse functions including: regulation of intracellular Ca(2+) homeostasis, chaperone activity, steroid-mediated gene regulation, and cell adhesion. To understand the physiological function of calreticulin we used gene targeting to create a knockout mouse for calreticulin. Mice homozygous for the calreticulin gene disruption developed omphalocele (failure of absorption of the umbilical hernia) and showed a marked decrease in ventricular wall thickness and deep intertrabecular recesses in the ventricular walls. Transgenic mice expressing a green fluorescent protein reporter gene under the control of the calreticulin promoter were used to show that the calreticulin gene is highly activated in the cardiovascular system during the early stages of cardiac development. Calreticulin protein is also highly expressed in the developing heart, but it is only a minor component of the mature heart. Bradykinin-induced Ca(2+) release by the InsP(3)-dependent pathway was inhibited in crt (−/−) cells, suggesting that calreticulin plays a role in Ca(2+) homeostasis. Calreticulin-deficient cells also exhibited impaired nuclear import of nuclear factor of activated T cell (NF-AT3) transcription factor indicating that calreticulin plays a role in cardiac development as a component of the Ca(2+)/calcineurin/NF-AT/GATA-4 transcription pathway.